ANALISIS PENGGUNAAN HURUF KAPITAL DAN TANDA BACA PADA KARANGAN NARASI SISWA KELAS V SD NEGERI 187 PEKANBARU - Arum Tri Kusumawati; Otang Kurniaman; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study analyzes the use of capital letters and punctuation on a narrative essay in students class V of SD Negeri 187 Pekanbaru. The problem in this research was the students write not in accordance with the rules of capitalization and punctuation predetermined EYD. This study aims to determine the use of capital letters and punctuation on a narrative essay in students class V of SD Negeri 187 Pekanbaru. This research method was a descriptive quantitative method which is in this study the researcher describes and interprets the object in accordance with what it is as well served in terms of numbers (percentage). The use of capital letters and punctuation in this study was a limited in accordance with the use of students in the essay that has been made. The use of capital letters was limited to 5 aspects: the capital letters are used as the first letter in the beginning of the sentence, as an elements of people's names, as the names of months, days, holidays and historical events, as a distinctive name in geography, and as the title essay except words like, to, from, and, and for that lies not in the starting position. The use of punctuation was limited to 5 aspects, namely pullstop at the end of a sentence that was not the question or exclamation, pullstop to separate the numbers, hours, minutes, and seconds which shows the time, a comma is used between elements in a subsection or numeration, conjuction in connecting apart of syllables by commutation line, and conjuction in connecting elements of repetition words.Keywords: capital letters, punctuation, narrative essay